Genome-wide repression of eRNA and target gene loci by the ETV6-RUNX1 fusion in acute leukemia - Teppo, Susanna; Laukkanen, Saara; Liuksiala, Thomas; Nordlund, Jessica; Oittinen, Mikko; Teittinen, Kaisa; Grönroos, Toni; St-Onge, Pascal; Sinnett, Daniel; Syvänen, Ann-Christine; Nykter, Matti; Viiri, Keijo; et al. (Genome Research, 2016)
Approximately 20%–25% of childhood acute lymphoblastic leukemias carry the ETV6-RUNX1 (E/R) fusion gene, a fusion of two central hematopoietic transcription factors, ETV6 (TEL) and RUNX1 (AML1). Despite its prevalence, the exact genomic targets of E/R have remained elusive. We evaluated gene loci and enhancers targeted by E/R genome-wide in precursor B acute leukemia cells using global run-on sequencing (GRO-seq). We show that expression of the E/R fusion leads to widespread repression of RUNX1 motif–containing enhancers at its target gene loci. Moreover, multiple super-enhancers from the CD19+/CD20+-lineage were repressed, implicating a role in impediment of lineage commitment. In effect, the expression of several genes involved in B cell signaling and adhesion was down-regulated, and the repression depended on the wild-type DNA-binding Runt domain of RUNX1. We also identified a number of E/R-regulated annotated and de novo noncoding genes. The results provide a comprehensive genome-wide mapping between E/R-regulated key regulatory elements and genes in precursor B cell leukemia that disrupt normal B lymphopoiesis.